2018
DOI: 10.1073/pnas.1720000115
|View full text |Cite
|
Sign up to set email alerts
|

Spatially constrained tandem bromodomain inhibition bolsters sustained repression of BRD4 transcriptional activity for TNBC cell growth

Abstract: The importance of BET protein BRD4 in gene transcription is well recognized through the study of chemical modulation of its characteristic tandem bromodomain (BrD) binding to lysine-acetylated histones and transcription factors. However, while monovalent inhibition of BRD4 by BET BrD inhibitors such as JQ1 blocks growth of hematopoietic cancers, it is much less effective generally in solid tumors. Here, we report a thienodiazepine-based bivalent BrD inhibitor, MS645, that affords spatially constrained tandem B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…Our SAXS-guided Rosetta modeling indicated that the Brd4 tandem bromodomains may access conformations in which the two acetyl-lysine binding sites reside as little as 15 Å apart, perhaps allowing for bivalent binding toward adjacent acetylation sites on individual histone tails. These results are consistent with the known ability of bivalent BET bromodomain inhibitors to simultaneously engage both acetyl-lysine binding sites (59, 74, 75). Previous studies of the Taf1 tandem bromodomains demonstrated 8-to 29-fold tighter binding affinity toward diacetylated ( K d = 1.4 to 5.3 µ M) relative to monoacetylated histone H4 tail mimic peptides ( K d ∼40 µ M) and proposed a model in which the two Taf1 bromodomains bivalently engage separate acetyl-lysine residues on a single peptide.…”
Section: Discussionsupporting
confidence: 89%
“…Our SAXS-guided Rosetta modeling indicated that the Brd4 tandem bromodomains may access conformations in which the two acetyl-lysine binding sites reside as little as 15 Å apart, perhaps allowing for bivalent binding toward adjacent acetylation sites on individual histone tails. These results are consistent with the known ability of bivalent BET bromodomain inhibitors to simultaneously engage both acetyl-lysine binding sites (59, 74, 75). Previous studies of the Taf1 tandem bromodomains demonstrated 8-to 29-fold tighter binding affinity toward diacetylated ( K d = 1.4 to 5.3 µ M) relative to monoacetylated histone H4 tail mimic peptides ( K d ∼40 µ M) and proposed a model in which the two Taf1 bromodomains bivalently engage separate acetyl-lysine residues on a single peptide.…”
Section: Discussionsupporting
confidence: 89%
“…The experiment was performed as previously described [44]. Briefly, PC3 cells were treated with an increasing amount of C10 and DMSO for 1 h at 37 • C. Following this, the cells were washed with PBS, heated at 49 • C for 5 min, placed at room temperature for 3 min, and treated with liquid nitrogen (−37 • C) water-bath cycles three times.…”
Section: Cellular Thermal Shift Assaymentioning
confidence: 99%
“…But it is noteworthy to mention that the currently available BET inhibitors as single agents, despite their promising anti-cancer activity in animal models, seem to only exhibit limited efficacy in clinical trials 53 . To address potential issues of low potency, next-generation BET-inhibiting compounds are being developed, such as bivalent BET inhibitors that bind to tandem bromodomains simultaneously and PROTAC-based BET degraders, which offer superior therapeutic effects in preclinical studies 54 57 . In addition, combination therapy with other synergistic anti-cancer drugs was reported to greatly boost the efficacy of BET inhibition and prevent emergency of drug resistance 58 , 59 .…”
Section: Discussionmentioning
confidence: 99%